A study on livelihood capital, social adaptation, and life satisfaction—empirical analysis based on ecological migration in the Kalajun world natural heritage site - Hu, Jiran; Yao, Juan; Xiong, Changjiang (Frontiers in Environmental Science, 2023)
Improving the life satisfaction of ecological migrants is important for promoting the construction of an ecological civilisation. Based on using sustainable livelihood theory and social adaptation theory to construct an analytical framework for life satisfaction, we innovatively include livelihood capital, social adaptation, and life satisfaction in the same research framework. Using microscopic research data on Kazakh herders in Kalajun, Xinjiang, we empirically analyse the effects of livelihood capital and social adaptation on herders’ life satisfaction using structural equation modelling and further discuss the direct and indirect effects of livelihood capital on life satisfaction. The results show that, first, the mean value of livelihood capital of the sample herding households is below the medium level overall, the mean value of social adaptation is above the medium level, and the life satisfaction of herders is above the medium level. Thus, the ecological migration policy has enhanced the herders’ life satisfaction to a certain extent. Second, financial and natural capital contribute more to the level of livelihood capital, while cultural, life, and psychological adaptation contribute more to the level of social adaptation. Third, both livelihood capital and social adaptation have a significant positive effect on pastoralists’ life satisfaction, i.e., the higher the level of livelihood capital and social adaptation of pastoralists, the more prominent their livelihood capacity and social relations are, and the higher their life satisfaction will be. Fourth, the direct effect of social adaptation on life satisfaction is significantly greater than that of livelihood capital; this should be used to alleviate psychological stress by enhancing herders’ social adaptation abilities. Fifth, the direct impact of livelihood capital on life satisfaction is greater than its indirect impact, and the improvement in human and financial capital will help herders overcome their current livelihood difficulties. The findings of this study will help the government understand the level of livelihood capital and social adaptation of ecological migrant households and provide a reference for further improving ecological migrants’ wellbeing and promoting sustainable regional development.